Gastrointestinal Parasites in Iberian Wolf (Canis lupus signatus) from the Iberian Peninsula - Pereira, Ana Luísa; Mateus, Teresa Letra; Llaneza, Luis; Vieira-Pinto, M. M.; Madeira de Carvalho, L. M. (Parasitologia, 2023)
[Abstract]: The Iberian Peninsula is one of the most humanized areas in Europe, yet humans may cohabit with large predators, such as the Iberian wolf (Canis lupus signatus), at the expense of many contributions to its conservation. The limited wolves’ territory leads to a close relationship between this wild species, humans, and other animals, which may promote the spillover of pathogens, such as gastrointestinal parasites. This review intends to provide an update concerning gastrointestinal parasite findings performed using coprological methods on fecal samples from Iberian wolves. Studies conducted in Portugal and Spain through coprology presented a prevalence of gastrointestinal parasites of 57.0–100% in Spain and 21.5–68.3% in Portugal. Parasites belonging to Protozoa, Trematoda, Cestoda, and Nematoda were specified, alongside thirteen genera and twenty species of gastrointestinal parasites. In this study, 76.9% (10/13) of genera and 65.0% (13/20) of species of gastrointestinal parasites were identified as having zoonotic potential. These results highlight that further studies are needed to better understand the parasitic agents circulating in the wild in humanized areas, such as the Iberian Peninsula. This research was supported by CIISA/FMV Project UIDB/00276/2020 and Project LA/P/0059/2020-AL4AnimalS (both funded by the Portuguese Foundation for Science and Technology (FCT)) and CIVG, Vasco da Gama University Research Centre. The participation of Teresa Letra Mateus and Maria Madalena Vieira-Pinto was supported by Project UIDB/CVT/00772/2020 and Project LA/P/0059/2020, respectively, funded by the FCT. All authors are grateful to the two reviewers who provided useful comments that helped to improve the quality of the manuscript. Fundação para a Ciência e a Tecnologia; UIDB/00276/2020 Fundação para a Ciência e a Tecnologia; LA/P/0059/2020-AL4AnimalS Fundação para a Ciência e a Tecnologia; UIDB/CVT/00772/2020 Fundação para a Ciência e a Tecnologia; LA/P/0059/2020